The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1361-6587/ac35ee
|View full text |Cite
|
Sign up to set email alerts
|

Simulating fusion alpha heating in a stellarator reactor

Abstract: Gyrocenter following simulations of fusion born alpha particles in a stellarator reactor are preformed using the BEAMS3D code. The Wendelstein 7-X high mirror configuration is scaled in geometry and magnetic field to reactor relevant parameters. A 2 × 10 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…To further study the mechanisms for the deviations in J , we perform GC integration in several vacuum equilibria that are optimized for quasiaxisymmetry on the boundary [58] in addition to having a value of ι = 0.52 on the boundary and aspect ratio 6. For the base equilibrium, the optimization is terminated when the quasisymmetry on the boundary is f QS = 1.8 × 10 −2 , see (9). We compare with two other equilibria, for which the optimization is terminated at f QS = 1.8 × 10 −3 and f QS = 1.3 × 10 −4 .…”
Section: Diffusive Banana Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…To further study the mechanisms for the deviations in J , we perform GC integration in several vacuum equilibria that are optimized for quasiaxisymmetry on the boundary [58] in addition to having a value of ι = 0.52 on the boundary and aspect ratio 6. For the base equilibrium, the optimization is terminated when the quasisymmetry on the boundary is f QS = 1.8 × 10 −2 , see (9). We compare with two other equilibria, for which the optimization is terminated at f QS = 1.8 × 10 −3 and f QS = 1.3 × 10 −4 .…”
Section: Diffusive Banana Transportmentioning
confidence: 99%
“…The confinement of fusion-born alpha particles is largely determined by collisionless physics. Comparisons of collisionless with collisional alpha particle losses have found that pitchangle scattering effects are insignificant for losses before the slowing-down time of ≈0.05 seconds in a W7-X reactor configuration [9]. Generally, the difference between collisionless and collisional calculations is configuration dependent [10].…”
Section: Introductionmentioning
confidence: 99%
“…BEAMS3D's deposition model has been validated [30] and a preliminary validation and benchmarking of the slowing down model has been done [29]. The simulations for this work were done using a new feature created for BEAMS3D that models fusion births and uses the birth rates to initialize particles for simulation [19].…”
Section: Energetic Particle Simulationsmentioning
confidence: 99%
“…The weighting of each particle is then determined by the fusion birth rate at its initial location divided by the volume of its cell and the number of particles within. In this way, particles from the edge region, in which the birth rate is several orders of magnitude lower, can still be sampled [19].…”
Section: Energetic Particle Simulationsmentioning
confidence: 99%
See 1 more Smart Citation